Joy Moody is out of time - Mayne, Kerryn (St. Martin's Press, 2025)
"Strange things are happening behind the bright pink facade of Bayside's premier laundromat, Joyful Suds; home to Joy Moody and her twin daughters. For much of their lives, Joy has been lying to Cassie and Andie. What started as a colorful tale to explain how the twins came to live with her grew over the years and was always something she meant to set straight. Joy really did think she had more time. Worse still, Joy is struggling to define the truth from the lies. The girls have long believed they are vital to the future and must stay hidden to stay safe. Joy has told them that their impending 21st birthday is significant; they will step into their roles as leaders of a revolution and life as they know it will change. Joy was right -- everything will change, just not in the way they expected. On Andie and Cassie's birthday, Joy Moody is found dead and her girls face a world they are not prepared for without their mother. Joy Moody is out of time... in more ways than one." --